Sustainable peace building and development in Nigeria's post-amnesty programme: The role of corporate social responsibility in oil host communities - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
The activities and violence of militants in the Niger Delta which saw the capacity for production of oil in Nigeria fall to an all-time low resulted in the federal government of Nigeria (FGN) announcing the Presidential Amnesty Programme in return for peace in the region. We examine how multinational oil companies' (MOCs') corporate social responsibility (CSR) impact on entrepreneurship development and job creation to absorb the youths. 1200 youths were sampled across the nine states of Niger Delta. Results from the use of estimated logit model reveal that GMoU interventions are prevalent in communities with greater ownership, creating room for better projects, sustainability and improved trust; yet the interventions failed to make significant impact on entrepreneurship development and job creation. Clearly, facilitating how youths get involved in skill acquisition and empowerment programmes would help them become entrepreneurs, improving their self-assurance that they can prosper outside militancy activities and violence.
Keywords: 330; Presidential amnesty programme; multinational oil companies; corporate socialresponsibility; youths and entrepreneurship development; Nigeria